2009
DOI: 10.1519/jsc.0b013e31819d0932
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Seated and Standing Triple Wingate Tests

Abstract: Observations of athletes in seated and standing cycling positions in laboratory and field settings have led to the perception that they produce different outputs. The purpose of this study was to determine whether there are differences in power output and physiological responses between seated and standing positions of athletes during 3 consecutive Wingate tests. Seven (n = 7) elite-level speedskaters completed 3 x 30-second Wingate tests (resistance = 7.5% body weight) with 3.5 minutes of recovery between eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 8 publications
0
12
0
2
Order By: Relevance
“…These results are consistent with subsequent WATs performed with 3 minutes and 20 seconds of recovery. 36 Wilson et al 36 reported a power decline of 48% to 56% across participants who performed repeated conditions of the WAT on different days and cycling positions. Our results are also comparable to normative data of power declines reported for men (47% ± 7.6%) and women (42% ± 7.9%) in NCAA Division I sports.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with subsequent WATs performed with 3 minutes and 20 seconds of recovery. 36 Wilson et al 36 reported a power decline of 48% to 56% across participants who performed repeated conditions of the WAT on different days and cycling positions. Our results are also comparable to normative data of power declines reported for men (47% ± 7.6%) and women (42% ± 7.9%) in NCAA Division I sports.…”
Section: Discussionmentioning
confidence: 99%
“…Anyway, other variables, including some not specified by the researchers, may influence the results of the research. Those related to WAnT include: the type of warm-up before the test [75] as a warm-up with changes in pace that may help to improve performance later on in the test; resistance provided by the cicloergometer [76] as a type of resistance that is too low, such as the recommended 7.5% of body mass, may not help to achieve maximum performance; the time of day when the test is done [74], i.e., in the evening, may increase test performance; the change in position adopted by the subject in the cicloergometer during the test [77] may help to improve performance; the geometry of the bicycle [78] which, although it would seem to have no influence, has not as yet been subject to much study. As for the music used: the volume at which the music is played can influence performance [26], and a higher volume can be more motivating; the participants' previous experiences with music [10], because a song can recall moments and emotions for one subject but not for another; whether the music is their favorite or not [26,32], which can provide motivation; and generally speaking, their level of education (in six of the eight research cases, they were students, but level of education was not provided) [10].…”
Section: Strengths Limitations and Future Lines Of Researchmentioning
confidence: 99%
“…Therefore, the Wingate test (WT) is an anaerobic exercise test, most often performed on a stationary bicycle, that measures peak anaerobic power and anaerobic capacity 5 . It has been utilized in different populations 1,6,7 , especially to evaluate anaerobic performance in an all-out 30-s sprint (i.e., high-intensity effort). The data provided from this test are: peak power (PP), normally obtained in the initial seconds, average power generated during the test (AP), and the fatigue index (FI) which consists of performance reduction between the maximum and minimum power output 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The main recommendation in the execution of the WT is the position of the cyclist on the saddle, who should remain seated from the initial moment of acceleration of the pedals until the end of the test 8,9 . However, in race situations, there is a possibility of creating greater power according to the adopted position of the cyclist, that is, standing or seated 6,7 . Reiser et al 6 observed an increase in PP when the WT was conducted with the cyclist standing, although subsequent studies did not find an effect of position on power production 1,7 .…”
Section: Introductionmentioning
confidence: 99%